Leishmania infantum and Epstein-Barr virus co-infection in a patient with hemophagocytosis - Zied Gaifer; Mohamed-Rachid Boulassel (MDPI AG, 2017)
The authors describe a rare case of a 27-year old previously healthy male presenting with high grade fever, pancytopenia, hepatosplenomegaly, high levels of ferritin and triglyceride, suggesting a diagnosis of hemophagocytic lymphohistiocytosis (HLH) syndrome. Other investigations showed a positive Leishmania infantum serology and high Epstein-Barr virus (EBV) viremia. The diagnosis of a visceral leishmaniasis was confirmed by bone morrow biopsy, which showed Leishman-Donovan bodies and evidence of HLH. The patient received liposomal amphotericin B and he had a complete resolution of his symptoms and clearance of EBV viremia. This case of HLH associated with visceral leishmaniasis and EBV co-infection raises the question about the significance of EBV in patients with HLH. The treatment of actual etiological agent can lead to complete cure while using current recommend chemotherapy for HLH-related EBV in a patient with hidden infection may have deleterious effects.